STRATEGIC FLEXIBILITY AND ITS REFLECTION ON BANKING PERFORMANCE : AN ANALYTICAL STUDY IN IRAQ COMMERCIAL BANKS - Mr. Ali fakhir kadhim alwajid; Mr. Osamah jassim mohammed; Dr. Asahaq Naser Hussain (Scholar Express Journals, 2023)
This study aims to determine the impact of strategic flexibility on the dimensions of (production flexibility, competitive flexibility, market flexibility, human capital flexibility) and (financial perspective, customer perspective, operational perspective) that is reflected on the bank’s performance in representative dimensions, in addition to the learning perspective and growth). The problem of the study is that the performance of the bank for the study sample has shortcomings, and that strategic flexibility needs clarification to draw the attention of the study sample to the strategic importance of improving banks’ resilience by adapting to rapid environmental developments. Where (60) forms were distributed and (55) correct forms were retrieved for analysis, i.e. (92%) for analysis using ready-made statistical programs (V.Spss), as well as data and extraction of arithmetic mean, standard deviation, coefficient of variation and correlation coefficient. The statistical methods of correlation coefficient resulted in A set of results, the most important of which are: the existence of a statistically significant relationship between strategic flexibility and the bank’s performance, as well as there is an impact of strategic flexibility in banking performance, and this study came out with a set of conclusions, the most important of which was that strategic flexibility has received great importance and high attention by the Trade Bank of Iraq
Keywords: strategic flexibility; banking performance